Fragment-based target screening as an empirical approach to prioritising targets: a case study on antibacterials. Issue 11 (November 2020) - Canning, Peter; Birchall, Kristian; Kettleborough, Catherine A.; Merritt, Andy; Coombs, Peter J.
Highlights: Identification of ligandable antibacterial targets from an essential gene list. High-throughput protein production and fragment screening multiple targets in parallel. Using bioinformatics and empirical triage to select the best targets for drug discovery. Abstract : Here, we describe a novel workflow combining informatic and experimental approaches to enable evidence-based prioritising of targets from large sets in parallel. High-throughput protein production and biophysical fragment screening is used to identify those targets that are tractable and ligandable. As proof of concept we have applied this to a set of antibacterial targets comprising 146 essential genes. Of these targets, 51 were selected and 38 delivered results that allowed us to rank them by ligandability. The data obtained against these derisked targets have enabled rapid progression into structurally enabled drug discovery projects, demonstrating the practical value of the fragment-based target screening workflow. Teaser: Selecting the best targets for drug discovery projects by combining bioinformatics and an empirical tractability and ligandability approach with fragment-based target screening could offer a new way forward for drug discovery.